Grigor Ghapantsyan’s Onomastic Studies - DILBARYAN, NARINE (Bulletin of Yerevan University B: Philology, 2021)
Grigor Ghapantsyan is one of the greatest Armenian linguists of the beginning and middle of the 20th century, whose theories and opinions are relevant and actual until nowadays. He is one of the most quoted scientist-Armenologists whose works are very well-known abroad. G. Ghapantsyan’s range of scientific interests was rather wide. He carried out a lot of toponymic studies in which he explored not only the place names but also the anthroponyms, theonyms, patrimonial names. In general, the great scientist analyzed the toponymy of Armenian Highland and Asia Minor. He discovered the еtymology of the ethnonyms “Armen” and “Hay”. G. Ghapantsyan reconstructed the patrimonial names in the ancient toponyms, ethnonyms of those tribes which participated in the formation of the Armenian people, and on the basis of these tribes and their settlements, he restored the аncient homeland of Armenians, the relations of the Armenian language with the ancient Indo-European, Caucasian and Semitic languages. Ghapantsian’s most famous onomastic works аrе "Historical-Linguistic Significance of the Toponymy of Ancient Armenia" (1940), "Suffixes and Suffixal Elements in the Toponymy of Ancient Asia Minor" (1948). Later, his onomastic and philological studies were collected and published in the two-volume "Historical-Linguistic Works"( volume I -1956, volume II– 1975).